Factors affecting the assessment of ESL students' writing: a case study of UiTM English language lecturers / Puteri Nur Hidayah Kamaludin - Kamaludin, Puteri Nur Hidayah (2014)
This paper investigated the factors that could affect raters as they marked English as Second language students’ essays. It is imperative for educators to identify these factors as it could give negative effects to students’ performance in improving their English language. This is because the assessment of writing can help students to increase their English level of proficiency, therefore it is essential that the feedbacks given to students are valid and reliable. It is also the purpose for this research to identify the most influential factor and also to probe whether these factors related to raters’ gender and years of teaching. The participants for this research are 100 English language lecturers from Universiti Teknologi MARA (UiTM). They were later divided into 50 male lecturers and 50 female lecturers. This quantitative research used questionnaire that was self-constructed based on the literature review. Findings showed that rhetorical organisation is the most significant factor. Data also revealed that there are positive relationship between language and rhetorical organisation, and gender and years of teaching. These findings implied that these factors identified have some effects on raters when marking students’ essays and therefore will affect students’ performances and the reliability and validity of the marks given by the raters.